PENINGKATAN WAWASAN DAN JIWA KEWIRAUSAHAAN MAHASISWA MELALUI KOLABORASI ANTARA MAHASISWA DAN AUTO DETAILING SEBAGAI PRAKTISI USAHA - Wulan Rindyana Syafitri; Nahya Astriana; Danish Zulfan Al fathan (Taksasila Edukasi Insani, 2025)
This article was conducted as part of the assignment of the Entrepreneurship Application course to provide students with a practical understanding of the business operational process directly. The focus was directed to the autodetailing business of a vehicle owned by an alumnus of the University of Muhammadiyah Jakarta. The methods used were observation, interviews and literature studies which included business models, challenges, marketing strategies, and financial management. This business is run with a B2C business model that is oriented towards direct service to consumers, using the Business Model Canvas (BMC) framework. The main challenge in the form of limited initial capital is overcome by disciplined management of daily income. Marketing strategies are carried out through social media, community, and word of mouth, while financial management is implemented by separating business and personal funds, and calculating HPP and BEP as the basis for business decisions. This observation provides real insight into the importance of implementing entrepreneurial strategies to build a business sustainably in the midst of business competition.Keywords: Entrepreneurship, Business Learning, Auto Detailing, Business Model Canvas